Sub-Theme: Agile Bureaucracy and Dynamic Governance Critical Analysis on The Effectiveness of Bandung Corruption Court - Kristian Widya Wicaksono (Indonesian Association for Public Administration (IAPA), 2020)
This study seeks to understand the extent to which the Bandung Corruption Court (Bandung Tipikor Court) has accomplished the authority's enforcement. This research's scope includes two crucial aspects: (a) the capacity of resources to sustain the existence of Bandung Tipikor Court, and (b) Supervision and control over Bandung Tipikor Court by various judicial institutions. The method used in this analysis is a systematic literature review. The collected data are secondary data from a compilation of various literary works related to this paper and the results of observations on Bandung's Tipikor Court. The data obtained were then analyzed qualitatively by assessing the findings' accuracy and strength from various studies and comparing the results from those studies. This study's findings show that the Bandung Tipikor Court has not achieved the optimum standard for the enforcement of its authority since the funding for services and oversight and control is not adequate to enable the application of the authority held by the Bandung Tipikor Court.